PERFORMANCE OF KAZAKHSTAN’S AGRIFOOD MARKET - Bazhan Turebekova (Acta Scientiarum Polonorum. Oeconomia, 2017)
This paper focuses on foodmarket performance and analysis of Kazakhstan experiences with developing agriculture. In the paper the theoretic aspects of industry market performance, background of agriculture with emphasis on agrifood market is given. Examples from Kazakhstan’s experiences with development of the agrifood sector, and data from Kazakhstan Committee on Statistics are used. The result of analysis indicate that Kazakhstan has to develop the non-primary sector of the food supply chain in order to make it more competitive in global competition. Steps in this direction have already been taken by the agricultural policy of Kazakhstan. However, it is recommended that various issues must be addressed by the government, including the improvement of product quality and the creation of national brands, infrastructure development, creation of conditions for improving the technical support of agricultural production. Agriculture as the main activity of the rural population needs support. In this case indicators of agrifood market performance should be assessed.